The Impact of a Reentry and Aftercare Program on Recidivism - Colin Cannonier; Monica Galloway Burke; Ed Mitchell (Global Labor Organization (GLO), 2020)
In this paper, we explore the impact of a reentry and aftercare service program on the likelihood of returning to prison by ex-offenders. Using administrative data within a difference-in-differences design, we find that this social program is associated with a reduction in recidivism rates. Benchmark estimates show that the program was associated with estimated reductions in the probability of recidivating of 6.0 to 8.7 percentage points. The estimate appears to be economically significant as it implies an estimated treated effect in the 15.8 to 19.2 percent range. We consider the heterogeneous effects of the program on reducing recidivism according to race, age group and program type. The program helped to reduce recidivism among Whites but not Blacks; older participants were the main beneficiaries while the effectiveness of the program was observed amongst older participants. Back-of-the-envelope cost-savings analysis is incorporated to estimate the potential savings to the state arising from the reduction in recidivism rates likely attributable to the program. The findings are robust to sample selection bias, alternative specifications and estimation techniques. Our results offer some implications for the role of faith-based social programs within the context of criminal justice reform to combat reentry of former inmates. They also provide a cautionary tale about the need to evaluate programs not just based on their overall effect.
Keywords: H73; L31; 330; Difference-in-differences; prison; propensity score matching; recidivism; reentry and aftercare programs